Cyclic Behavior and Performance of U-Shaped Damper for Seismic-Resistant Design - Nguyen, Van-Tu; Nguyen, Xuan-Dai (Journal of Applied Nonlinear Dynamics, 2026)
Metallic yield damper has been considered a reliable solution for the seismic-resistant design and widely applied in recent years for construction engineering. The U-shaped device is one of the most commonly used metal yielding devices in practice, based on its benefits such as low-cost, flexible application, and high-efficiency. However, the large plastic deformation during loading making it is difficult to predict its behavior and assess its seismic performance, especially in the practical design, where a suitable estimated behavior of the device is needed. This paper aims to investigate the seismic performance of the U-shaped damper subjected to the cyclic loading in different operating directions and gives approximate formulas to estimate its nonlinear behavior for its selection and sizing in the preliminary design. Analytical procedures and 3D finite element analyses are carried out to determine the variability of the device parameters with various effects, including geometrical parameters, displacement amplitudes, and operating directions. The results present a high seismic performance of the U-shaped damper based on its great plastic deformation capacity. The best efficiency of the device corresponds to the in-plane operation. Furthermore, an approximate prediction of the nonlinear behavior of U-shaped dampers is proposed for the two orthogonal operating directions of the device by the equivalent bilinear hysteresis. The material properties, geometrical parameters, and deformation rates are considered the key parameters to predict the hysteretic behavior of the U-shaped device.